2014
DOI: 10.1016/j.jneuroim.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the accumulation of co-infiltrating CNS dendritic cells and encephalitogenic T cells during EAE

Abstract: Evidence from experimental autoimmune encephalomyelitis (EAE) suggests that CNS-infiltrating dendritic cells (DCs) are crucial for restimulation of coinfiltrating T cells. Here we systematically quantified and visualized the distribution and interaction of CNS DCs and T cells during EAE. We report marked periventricular accumulation of DCs and myelin-specific T cells during EAE disease onset prior to accumulation in the spinal cord, indicating that the choroid plexus-CSF axis is a CNS entry portal. Moreover, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…The possibility was raised that NG2 null macrophages may exhibit less inflammatory properties than their WT counterparts [ 28 ], leading to a reduced ability to invade the CNS [ 30 ], and such a feature would support the lower extent of inflammation in NG2KO CNS during EAE. To determine if the possible role of NG2 in inflammation might also be relevant for other inflammatory cells that are liable to infiltrate the CNS during EAE [ 7 , 56 ], we sought to ascertain whether NG2 is expressed in WT mice or not by cells of the systemic immune system. We assessed the expression of NG2 by T cells in freshly isolated splenocytes and by bone-marrow-derived dendritic cells (BMDDCs) and macrophages (BMDMs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility was raised that NG2 null macrophages may exhibit less inflammatory properties than their WT counterparts [ 28 ], leading to a reduced ability to invade the CNS [ 30 ], and such a feature would support the lower extent of inflammation in NG2KO CNS during EAE. To determine if the possible role of NG2 in inflammation might also be relevant for other inflammatory cells that are liable to infiltrate the CNS during EAE [ 7 , 56 ], we sought to ascertain whether NG2 is expressed in WT mice or not by cells of the systemic immune system. We assessed the expression of NG2 by T cells in freshly isolated splenocytes and by bone-marrow-derived dendritic cells (BMDDCs) and macrophages (BMDMs).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is likely that the skewing from Th1 to Th2 in MOG35-55-responsive NG2KO T cells is also related to a role of NG2 in DC activation. DCs are the main antigen-presenting cells in EAE [ 18 ], co-infiltrating the CNS with T cells [ 7 ]; their production of IL-12 is essential in the Th1-cell response implicated in the disease. IL-12 is a potent inducer of IFN-γ secretion by T cells; it drives the differentiation of naïve T cells to Th1 cells while impeding that to Th2 cells, and contributes to amplification and expansion of Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from different laboratories suggest that CNS immune cells are activated before the appearance of clinical symptoms of MS and before T cell infiltration. For example, work from Dr. Fabry’s group demonstrated activation of microglia and CNS DCs ahead of the infiltration of MOG-specific T cells in the olfactory bulb ( 32 , 33 ), cerebellum, and along the white matter tracts ( 34 ). The activation of these cells was specific to EAE and was significantly increased compared to healthy mice and CFA-injected controls.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…However, a recent work using the developmental and functional criteria demonstrated that DCs develop from their precursors (pre-DCs) in the meninges and choroid plexus of mice ( 56 ). In the case of neuroinflammation due to injury or infection, the BBB gets compromised and peripheral DCs infiltrate the CNS ( 55 ), where they contribute to antigen presentation and reactivation of encephalitogenic T cells ( 34 , 57 ). Several studies also demonstrated the accumulation of DCs in white matter lesions and cerebrospinal fluid (CSF) of MS patients ( 58 , 59 ).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…However, this cellular population is largely, but not entirely, absent from the brain parenchyma in the steady state [18-24]. There is evidence that the minimal population of CNS resident DCs can be further augmented by additional DCs migrating into the brain during periods of inflammation [25, 26]. In contrast, macrophages (MΦs) in the perivascular spaces and microglia in the parenchyma are, at least numerically, the predominant APCs within the CNS.…”
Section: Introductionmentioning
confidence: 99%